NEMATODE PARASITES OF WATERLEAF (Talinum triangulare) IN OBIO-AKPOR AND IKWERRE LOCAL GOVERNMENT AREAS OF RIVERS STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Waterleaf, Talinum triangulare is cultivated in home gardens and fields to improve nutritional quality for the family and a source of livelihood for farmers. However, the role of T. triangulare is often counteracted by plant-parasitic nematodes (PPNs). Effective management of PPNs will depend on the identification and determination of their population and distribution. A survey was conducted in two Local Government Areas (LGAs), Ikwerre and Obio-Akpor of Rivers State to identify plant-parasitic nematodes associated with waterleaf. Multistage random sampling technique was employed in the collection of 60 bulked soil and root samples across six waterleaf monoculture farming communities. The nematodes were extracted, identified and their population determined using standard procedures. Occurrences, relative importance values (RIV) and diversity indices were determined. Other data were analysed using descriptive statistics and analysis of variance. Six plant-parasitic nematodes genera were encountered in this study, Helicotylenchus, Pratylenchus, Paratylenchus, Meloidogyne, Scutellonema and Tylenchulus. Pratylenchus and Helicotylenchus were the most frequently occurring nematode pest genera with equal relative frequency of occurrence of 38.89%. Pratylenchus species with RIV of 61.34% was the most important nematode pest associated with waterleaf across the six farm communities. The dominance index of 0.71 for the nematode genera showed that some nematode species dominated others. Alakahia farms had the highest population of plant-parasitic nematodes (2,780) across the six farm communities, whereas Omagwa farms had the lowest (250). The study showed that nematode pests are associated with waterleaf and could be contributing to yield losses in this crop
Keywords: Diversity indices, Nematode pests, Occurrence, Waterleaf, Survey